STRATEGY TO IMPROVE ADMINISTRATIVE SERVICES AT THE OFFICE OF RELIGIOUS AFFAIRS, NORTH GALESONG DISTRICT, TAKALAR INDONESIA - Nawir Rahman; Nurfadilah Fajri Hurriyah; Risma Niswaty; Sitti Hardiyanti Arhas (Bajang Institute, 2022)
This study aims to determine the strategy for improving administrative services at the Office of Religious Affairs, North Galesong District, Takalar Regency. This type of research is descriptive research with a qualitative approach. Data collection techniques were carried out through observation, interviews and documentation. The data analysis technique used consisted of data condensation, data presentation and conclusion drawing. The results showed that the Strategy for Increasing Administrative Services at the Office of Religious Affairs, North Galesong District, Takalar Regency can be seen from five service improvement strategies, namely (1) Core Strategy, all employees have understood the goals and functions and their respective duties are in accordance with SOP, several types of services are not implemented due to Covid-19. (2) Consequences Strategy, does not apply a reward system, the community appreciates (reward) employees who help them voluntarily, minimizing sanctions. (3) Customer Strategy, services provided are based on needs, services are in accordance with SOPs, implementon line systems on the SIMKAH application, facilities are available, security guarantees and one-stop services. (4) Control Strategy (Supervision Strategy), having full trust in employees, conveying and finding out what the community needs in administrative services at the Religious Affairs Office at every meeting at the local Camat Office or Village Office. (5) Culture Strategy, building team work, holding regular evaluation meetings and with disciplined leaders able to improve administrative services. The supporting and inhibiting factors can be seen in the awareness factor, organization and service facilities.